All or nothing : how Trump recaptured America [large type] - Wolff, Michael, 1953- (Random House Large Print, 2025)
"In his latest book, #1 New York Times bestselling author of Fire and Fury delivers a breathtaking insider account of the 2024 Trump campaign -- undoubtedly the wildest, most unpredictable campaign in U.S. history, including multiple criminal trials, two assassination attempts, and a sudden switch of opponents. All or Nothing takes readers on a journey accompanying Donald Trump on his return to power as only Michael Wolff, the foremost chronicler of the Trump era, can do it. As Trump cruelly and swiftly dispatches his opponents, heaps fire and fury on the prosecutors and judges who are pursuing him, and mocks and belittles anyone in his way, including the president of the United States, this becomes not just another election but perhaps, both sides say, the last election. The stakes could not be clearer: Either the establishment destroys Donald Trump, or he destroys the establishment. What soon emerges is a split-screen reality: On one side, a picture that could not be worse for Trump: an inescapable, perhaps mortal legal quagmire; on the other side, an entirely positive political outlook: overwhelming support within his party, ever-rising polling numbers, and lackluster opposition. Through personal access to Trump's inner circle, Wolff details a behind-the-scenes, revealing landscape of Trumpworld and its unlikely cast of primary players as well as the candidate himself, the most successful figure in American politics since, arguably, Roosevelt, but who might easily seem to be raving mad. Threading a needle between tragedy and farce, the fate of the nation, the liberal ideal, and democracy itself, All or Nothing paints a gobsmacking portrait of a man whose behavior is so unimaginable, so uncontrolled, so unmindful of cause and effect, that it defeats all the structures and logic of civic life. And yet here in one of the most remarkable comebacks in American political history, Trump is victorious. This is not just a story about politics: It is a vivid exposé of the demons, discord, and anarchy -- the fire, fury, and future -- of American life under Trump." --